Biology of the Leafhopper, Acia lineatifrons (N aude) (Homoptera: Cicadellidae), on Grapevines in the Western Cape - Marais, Elleunorah (South African Journal of Enology and Viticulture, 2017)
The life history of Acia lineatifrons (Naude) was studied on potted grapevines. At a constant temperature of26°C the minimum pre-oviposition period of the females ranged from 5 -10 days, and the incubation period of the eggs from 9-11 days. The mean development time of the five nymphal instars from hatching to adult emergence was 15 and 25 days at 26° and 20°C respectively. Field studies showed that A. lineatifrons overwintered in the adult stage on indigenous Rubus spp. and entered the vineyard from late October to early November. Populations peaked between middle February and the end of March. During winter the sex ratio on rubus was heavily female biased, but during the growing season it was slightly male biased on both the rubus and grapevines. Adult leafhoppers showed a preference for grapevines to rubus in the laboratory, but field studies indicate that host preference is not the sole reason for the colonization of grapevines by leafhoppers.